2014
DOI: 10.1186/1471-2334-14-207
|View full text |Cite
|
Sign up to set email alerts
|

School closures during the 2009 influenza pandemic: national and local experiences

Abstract: BackgroundSchool closure is a non-pharmaceutical intervention that was considered in many national pandemic plans developed prior to the start of the influenza A(H1N1)pdm09 pandemic, and received considerable attention during the event. Here, we retrospectively review and compare national and local experiences with school closures in several countries during the A(H1N1)pdm09 pandemic. Our intention is not to make a systematic review of country experiences; rather, it is to present the diversity of school closu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
99
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 26 publications
(21 reference statements)
2
99
0
1
Order By: Relevance
“…compared to adults are expected to be more sensitive to the closure of schools [9]. This experience was reported in many countries during the 2009 H1N1 influenza pandemic, where closed schools coincided with a marked reduction of influenza activity [10][11][12][13][14][15][16][17][18][19][20][21][22].…”
mentioning
confidence: 99%
“…compared to adults are expected to be more sensitive to the closure of schools [9]. This experience was reported in many countries during the 2009 H1N1 influenza pandemic, where closed schools coincided with a marked reduction of influenza activity [10][11][12][13][14][15][16][17][18][19][20][21][22].…”
mentioning
confidence: 99%
“…6 Since that study was conducted, 2 studies have examined K-12 schools and biological events. One study consisted of an international review of school closure policies and procedures related to the 2009 H1N1 pandemic, 9 and the other study examined differences across local health department implementation of school-based vaccination clinics. 10 No study has examined the extent to which schools are prepared for natural disasters or pandemics since the nationwide 2011 study.…”
mentioning
confidence: 99%
“…Klaiman et al reported that pre‐event mass vaccination exercises in schools made deployment of actual school‐based vaccination clinics easier during the H1N1 influenza pandemic. Cauchemez et al asserted that schools need to host a drill to discuss policies and practices related to school closures during pandemics.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, serious pandemic planning gaps were identified, such as failure to address pandemics in school disaster plans, to stockpile medication and personal protective equipment (PPE), and to incorporate infectious disease scenarios into school disaster drills . Few researchers have examined school disaster preparedness since, with the exception of studies focusing on the impact of the H1N1 influenza pandemic . One study found planning for school closures due to pandemics was insufficient and recommended specific actions, such as deciding on thresholds for closure, on methodologies for distance‐based education, and on materials for communicating with parents, staff, and the media .…”
mentioning
confidence: 99%
See 1 more Smart Citation